Profil Koneksi Matematis Siswa SMP Negeri 4 Sigi Kelas IX Pada Materi Bangun Ruang Ditinjau dari Kemampuan Matematika - Mutiara Mutiara; Muh Rizal; Fajriani Fajriani; Nurhayadi Nurhayadi (Aksioma, 2026)
This qualitative descriptive research aims to describe the mathematical connections of 9th-grade students at SMP Negeri 4 Sigi regarding spatial shapes based on their mathematical ability levels. Data were collected through written tests and interviews to explore students' understanding in depth. The results indicate that students with high mathematical ability are capable of connecting surface area with the area of a rectangle, converting diameter to radius in volume calculations, and systematically linking the concepts of area and volume. They can effectively apply mathematics to other disciplines and real-life contexts. Students with moderate ability demonstrate similar skills in connecting surface area, volume, and daily applications, yet they tend to be less specific in identifying interdisciplinary connections, such as with economics. Meanwhile, students with low ability are able to determine surface area and provide real-life examples, but they encounter difficulties in relating surface area to the concept of a rectangle's area and are unable to identify interdisciplinary relationships in written tests. Overall, there are significant differences in the depth of mathematical connections and systematic procedural abilities among the three groups of students in solving spatial shape problems.